Finite element method modeling Fukui sheet metal formability test - Ammar, Ismail @ Mukhtar (2009)
The main objective of this project is to create Fukui conical cup model using finite element method to investigate the formability of sheet metal. The Fukui testing involved both deformation drawing and stretching. The elastic and plastic material properties are testing with plane stress and axis symmetric. There are three types of material aluminium, brass and steel are used to this project. The project begins with die design with AutoCAD and Solidworks. The project is further to modeling finite element with Algor FEA. The simulation started with elastic and plastic material model with plane stress. Then the material model is changed to axis symmetric with elastic and plastic material. The data collection taken to making graph of displacement. The simulation taken different time for each material. The variables for this project are variety of sheet metal and geometry type plane stress and axis symmetric. The constant of this simulation are thickness of sheet metal and displacement of the indenter to deform the material. All the data from Algor’s software will show the different value of displacement when transferred to Microsoft Excel. The axisymmetric geometry type shown the data are not too overlapping each other compare to plane stress. From the data documentation, the discussion and result were conclude for making the developing Fukui conical cup sheet metal formability modeling.